Happily Religious: The Surprising Sources of Happiness Among Lesbian, Gay, Bisexual, and Transgender Adults. Issue 1 (2nd December 2016) - Barringer, M. N.; Gay, David A.
Abstract : This article analyzes the impact of religion on reported levels of subjective well‐being (general happiness) among lesbian, gay, bisexual, and transgender (LGBT) adults. Although previous studies find religious affiliation to be a significant predictor of subjective well‐being among the general population in the United States, limited quantitative research investigates general happiness among sexual and gender minorities. This study augments the existing literature by using a national survey of LGBT adults conducted by the Pew Research Center in 2013. The results show that religious affiliation is a significant predictor of LGBT individuals' happiness. LGBT individuals who identify as Catholic, agnostic or atheist, or with no particular religious affiliation report lower levels of happiness compared to mainline Protestants. Surprisingly, no significant differences are found between mainline Protestants (whose church doctrine often accepts same‐sex relations) and evangelical Protestants (whose church doctrine often condemns same‐sex relations). In addition, income is the only control variable that affects general happiness. Our analysis reveals interesting differences in the determinants of subjective well‐being between the LGBT and general population.